2012
DOI: 10.7883/yoken.65.318
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infections in the General Pediatric Wards of a Hospital in Turkey

Abstract: SUMMARY:The aims of this study were to determine the prevalence, type, and clinical features of nosocomial infections (NIs), their etiological distribution, and the antibiotic resistance patterns of causative organisms in the general pediatric wards of a hospital in Turkey over a 3-year period. The Hospital Infection Control Committee NI surveillance reports were used as a database. NIs were detected in 171 (2.25z) of the 7,594 hospitalized patients. Some of these patients experienced more than 1 episode, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…Similar to the present study, most of the studies found VAP as the most frequent NIs (4,7,12,13,20) and other studies reported analogous rates of NIs in Argentina and Latin American countries (5, 7). Although some studies detected that UTI was the most prevalent NIs (11,21), it is considerable that researches distinguished higher prevalence of NIs in university hospitals (20,22). UTI prevalence in the current study was the third most common type of infection similar to large surveillance program reports across Europe (23).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to the present study, most of the studies found VAP as the most frequent NIs (4,7,12,13,20) and other studies reported analogous rates of NIs in Argentina and Latin American countries (5, 7). Although some studies detected that UTI was the most prevalent NIs (11,21), it is considerable that researches distinguished higher prevalence of NIs in university hospitals (20,22). UTI prevalence in the current study was the third most common type of infection similar to large surveillance program reports across Europe (23).…”
Section: Discussionsupporting
confidence: 74%
“…Along with the significant relationship between NIs and mortality, the maximal risk of NIs belonged to patients with BSI and UTI in the present study. Although it is reported that VAP had the highest rate of mortality (21,22), some authors reported lower mortality rates for BSI and UTI patients (22,26). These various reported observations may be due to different sampling, classification and diagnosis of the associated underlying data, calculation methods, inclusion and exclusion criteria, studied population and race, geographic regions, lifestyle, and dietary habits.…”
Section: Discussionmentioning
confidence: 97%
“…An even more dramatic difference was observed among nosocomial infections (NIs) in a general pediatric hospital in Turkey, where Gram-negative pathogens accounted for 79.8% of cultured pathogens among 229 NIs; the most common pathogens identified were Klebsiella spp. (28.7%), P. aeruginosa (19.1%), and E. coli (9.6%) (13).…”
Section: Discussionmentioning
confidence: 99%
“…But study conducted by Mayhall, C.G. in USA [14], and a study done by Balaban, I., et al in Turkey shows that the commonest pathogens were gram-negative bacteria [15].…”
Section: Bacteriological Infectionsmentioning
confidence: 99%